2014
DOI: 10.2298/tsci120719003n
|View full text |Cite
|
Sign up to set email alerts
|

Cutting temperature measurement and material machinability

Abstract: Cutting temperature is very important parameter of cutting process. Around 90% of heat generated during cutting process is then away by sawdust, and the rest is transferred to the tool and workpiece. In this research cutting temperature was measured with artificial thermocouples and question of investigation of metal machinability from aspect of cutting temperature was analyzed. For investigation of material machinability during turning artificial thermocouple was placed just below the cuttin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The thermocouple was placed into a hole drilled from underside of the tool which through the tip goes out to the face surface at 0.6 mm far from the cutting edge. The hole accommodates the thermocouple S-type (Pt + 10% Rh) with wire diameters 0.05 mm [18].…”
Section: Calculation Of Temperature Fields By Using Finite Element Mementioning
confidence: 99%
“…The thermocouple was placed into a hole drilled from underside of the tool which through the tip goes out to the face surface at 0.6 mm far from the cutting edge. The hole accommodates the thermocouple S-type (Pt + 10% Rh) with wire diameters 0.05 mm [18].…”
Section: Calculation Of Temperature Fields By Using Finite Element Mementioning
confidence: 99%
“…The aim of this heading is to attempt a review of the contents of those works and consequently their comprehensive application. Nedic & Eric (2014) worked on temperature measurement technique known as tool-work thermocouple. This method is based on the principle that two metals, when they are in contact, produce a small amount of voltage which is proportional to temperature variation.…”
Section: Related Design Literaturementioning
confidence: 99%
“…According to Nedic & Eric (2014), metal cutting temperature was measured with artificial thermocouple and metal machine-ability was analyzed from aspect of cutting temperature. In Sui et al (2012), LM35 and PIC16F873 microcontroller was used to build a device which can measure safely the indoor temperature in firm buildings such as greenhouses, warehouses or silos.…”
Section: Related Design Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that if the tool's temperature is increased that leads to the acceleration of the wearing process. The high cost of specific cutting tools materials and the cost of downtime for tool changing must be minimized [7]. Tool wear plays a key role in the economy of machining operations.…”
Section: Introductionmentioning
confidence: 99%